PENGARUH KOMITMEN PROFESIONAL DAN LOCUS OF CONTROL AUDITOR INTERNAL TERHADAP INTENSI MELAKUKAN WHISTLEBLOWING : KESADARAN ETIS SEBAGAI VARIABEL PEMODERASI (SURVEI PADA AUDITOR INTERNAL PADA PERBANKAN YOGYAKARTA) - , ESTER AYU H, Taufikur Rahman, S.E., M.B.A, Ak ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to examine the influence of internal auditorâs professional commitment and locus of control toward whistleblowing intention and also to examine the impact of ethic awearness as moderating variable. The populations of this research is all of internal auditors who worked in banking company that status limited liability (PT) in Yogyakarta, which in this research the amount of them is unknown. This research uses purposive sampling technique to collect sample. Data were collected using a survey method that taken from questionaires distributed to 33 respondents and then analyzed by using linier regression analysis and hierarchical regression analysis. The hypothesis of this research consists four hypothesis. This research found evidence that internal auditorâs professional commitment and locus of control have significance influence toward whistleblowing intention. In general, internal auditor in this research have internal locus of control. This research also found evidence that ethic awearness as moderating variable influence the impact internal auditorâs professional commitment and locus of control toward whistleblowing intention. The results of this research implicated that personality aspects and cognitive style effect to internal auditorâs whistleblowing intention